2009
DOI: 10.1007/s00040-009-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Worker dominance and policing in the ant Temnothorax unifasciatus

Abstract: In many species of eusocial Hymenoptera, conflict about the production of males is resolved through ''policing.'' Recent studies in wasps and the ant Temnothorax unifasciatus suggest that in these species policing workers are dominant themselves and selfishly increase their own chances of later becoming fertile. Policing may therefore to some extent be associated with dominance and selfishness, and dominance and policing behaviour are indeed difficult to distinguish and often not mutually exclusive. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Third, worker discrimination of queen‐ and worker‐laid male eggs occurs via workers' detection of chemical cues on eggs (Nanork et al 2007). One or more of these elements occurs widely in other eusocial Hymenoptera exhibiting worker policing (e.g., Kikuta and Tsuji 1999; Endler et al 2004; Bonckaert et al 2008; Brunner and Heinze 2009). However, outside Apis , the cooccurrence of these three elements of classical worker policing has not been demonstrated.…”
mentioning
confidence: 99%
“…Third, worker discrimination of queen‐ and worker‐laid male eggs occurs via workers' detection of chemical cues on eggs (Nanork et al 2007). One or more of these elements occurs widely in other eusocial Hymenoptera exhibiting worker policing (e.g., Kikuta and Tsuji 1999; Endler et al 2004; Bonckaert et al 2008; Brunner and Heinze 2009). However, outside Apis , the cooccurrence of these three elements of classical worker policing has not been demonstrated.…”
mentioning
confidence: 99%
“…This is presumably not due to the ploidy of eggs, as the development times of haploid and diploid eggs in ants and other Hymenoptera appear to differ only marginally if at all [48][49][50] . The observed difference might rather stem from intra-colonial conflicts, in that egg eating associated with dominance behavior and worker policing might have caused a frequent exchange of newly produced eggs during the initial phase 19,29 .…”
Section: Discussionmentioning
confidence: 98%
“…Colonies of Temnothorax nest in spatially limited cavities in rock cracks, rotting branches, or hollow acorns, and in summer often space out to multiple nests [21][22][23][24][25][26][27][28] . In queenless conditions, Temnothorax workers form rank orders by antennal boxing and biting and only the highest ranking workers lay unfertilized, male-destined eggs 19,[29][30][31][32] . Genetic analyses revealed that in both queenless and queenright colonies of T. crassispinus about 20% of the males are not offspring of the queen 33,34 .…”
mentioning
confidence: 99%
“…In the time between queen loss and colony death, the social organization of the colony changes rapidly. Workers establish aggressive dominance hierarchies and high‐ranking workers begin to produce their own eggs (Brunner & Heinze, ; Stroeymeyt, Brunner, & Heinze, ), although some ants will continue to tend larvae for some time before they begin to lay their own eggs (Villalta, Angulo, Devers, Cerdá, & Boulay, ). This aggressive reorganization is energetically costly and the resulting shift in colony task participation can reduces worker life span (Gobin, Heinze, Strätz, & Roces, ; Tsuji, Kikuta, & Kikuchi, ).…”
Section: Introductionmentioning
confidence: 99%